Cultural-based challenges of the westernised approach to development in newly developed societies. Issue 5 (4th July 2019) - Zaidan, Esmat
ABSTRACT: Urban theorists and policymakers are increasingly recognising the importance of integrating culture into urban development models. This article provides a critical assessment of Dubai's integration of cultural planning in its approach to tourism development. It argues that western-influenced modernisation has side-lined indigenous creative resources in the pursuit of a cosmopolitan urban vision. Rapid urbanisation and westernisation of Dubai define and redefine the approaches for tourism development. The article suggests that embracing more culturally focused tourism plans may socially sustain local community and identity affected by rapid modernisation and westernisation in newly developed modern societies such as Dubai.